Joint towed streamer and ocean-bottom-seismometer data multi-parameter full waveform inversion in acoustic-elastic coupled media - Yang, Tao; Liu, Yuzhu; Yang, Jizhong (Frontiers in Earth Science, 2023)
Short-offset towed streamer data, and sparse ocean-bottom seismometer (OBS) data are not conducive to applying multi-parameter full waveform inversion (FWI) in production. It is challenging to reconstruct deep velocity in the former, and the latter suffers from severe acquisition footprints. We developed a joint acoustic-elastic coupled FWI (J-AEFWI) method, in which towed streamer data and OBS data were used jointly to build P-wave and S-wave velocity models. A new joint objective function was established using the least-squares theory, and the J-AEFWI method on the acoustic-elastic coupled equation was derived. The method can inject the residuals of the towed streamer data and the OBS data in time backward propagating to update P-wave and S-wave velocity models. The synthetic experimental results show that J-AEFWI obtains more accurate results than when using these two types of data alone. Compared to using the towed streamer or OBS data alone, the J-AEFWI method leads to better illumination of the deep background velocities and suppression of acquisition footprints. The results of J-AEFWI were slightly better than those of the cascaded FWI strategy. To further demonstrate the benefit of the proposed method, we applied it to the field data, and better results are obtained as expected.